Translation Mistakes of Arabic Poem into Tamil: The Undergraduates of the Department of Arabic Language, South Eastern University of Sri Lanka as a Model - Abdul Majeed Mohammed Aaqil; M.S. Zunoomy; U. Israth; M.H.A. Munas (Universitas Yudharta Pasuruan, 2022)
This study intends to pinpoint the mistakes made when translating the selected poetry into Tamil and to highlight the translation techniques used by South Eastern University of Sri Lanka's Department of Arabic language students. This research uses descriptive analytical methods. The data for this research was collected through the field and library. The primary data was collected from the questionnaires distributed among 100 third-year students from the Department of Arabic Language randomly. The library method consists of books, research, articles, and web articles. To obtain accurate scientific results, MS Excel is used. The findings of this study show that the students translated the poems to a medium level accurately. And they erred in these areas: selecting the appropriate words based on the poetic text's context; providing the proper meaning; determining the pronoun's reference; and considering the context of the source and target languages. They studied this poetry line by line, but regrettably missed the chance to apply. Due to this circumstance, they have limited knowledge of poetic works and a reluctance to study Arabic literature. Arabic literature lecturers must be proficient in the use of proper teaching strategies and get classroom work when studying poetic texts. For them to completely comprehend poetry texts, it is preferable to include background knowledge. This research finds that that students' mastery of translation criteria or requirements helps them to translate correctly.